The Effect Of Rotation, Earth Revolution To The Timing Of Salat - Muhalling, Rusdin (Advances in Social Sciences Research Journal, 2017)
This research is a study, study of astronomy as arithmetic, used by Muslims to practice their daily worship, especially praying, fasting, and pilgrimage to the temple of Mecca. The main subject is to determine the timing of praying, precisely and carefully based on data area and formulation of praying timing. The subject of this research is, the effect of rotation, earth revolution to the timing of prayer, done either by theory and practice, how the astronomy as an arithmetic, to determine sign of prayer time precisely and carefully in one place, Accuracy and precision can be proved and accountable scientifically based on the formulation of praying time. The timing of praying, early month of Ramadan, the first Syawal and Zulhijjah, as well as the timing of Aid Al-fitr and eid al-Adha, and the other great day for Muslims. The result of arithmetic and ruqyah can be proved and accountable scientifically. Research result showed that astronomy as arithmetic is so beneficial for Muslims to determine the timing of worship as to determine the beginning of Ramadan month, direction of Qiblah, set the time of breaking the fast and meal time. To set the beginning and ending of fasting Ramadan, To determining the day of Aid al-Fitr and Aid al-adha, direction of Qiblah in one area, started by the methods and practical ways, they are method of arithmetic (Hisab) and method of Ruqyah.